(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Economic crisis which has ravaged Indonesia since 1997 has some cffects on the ability of parents in financingtheir children’s education. The result is that the number of dropouts in each type and level of education has steadily increased. Another impact ofthe situation is theinvolzement ofso many school age children in various fields ofwork multingin their dropout. This situation has clearly shown that access to basic educationhas metsome constraints. To give equal opportunity to allpeople in education, Indonesian Government has adopted Education for all policy. This article is trying to expose the history of the movement Education for All, the desired goa4theprogress and constraints at a global scak, the condition of Educationfor Allmovementin Indcmesia, andwhateterze e can do about it